2022
DOI: 10.1002/cctc.202200800
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative Desulfurization Using MoO3 as Recyclable and Efficient Nanocatalyst

Abstract: Gathering clean energy from fuel feedstocks is of paramount significance in environmental science. In this area, desulfurization provides a valuable contribution by eliminating sulfur compounds from fuel feedstocks to ensure they can be used without emission of toxic sulfur oxides. MoO3 nanoparticles have been hydrothermally synthesized and used as efficient catalyst in the oxidative desulfurization (ODS) of methylphenyl and diphenyl sulfide using TBHP or H2O2 as oxidant. The catalyst showed an enhancement in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 41 publications
(112 reference statements)
0
3
0
Order By: Relevance
“…Theoretical calculations based on density functional theory were first conducted to investigate the mechanism of the ODS reaction over framework TiO 6 and TiO 4 sites. DMDBT has been selected as a model reactant molecule of ODS while tert-butyl hydroperoxide (TBHP, (CH 3 ) 3 COOH) is used as the oxidant because it is oil-soluble, highly oxidative, thermostable (>80°C) and used for industrial continuous processes [ 22–24 ]. As shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Theoretical calculations based on density functional theory were first conducted to investigate the mechanism of the ODS reaction over framework TiO 6 and TiO 4 sites. DMDBT has been selected as a model reactant molecule of ODS while tert-butyl hydroperoxide (TBHP, (CH 3 ) 3 COOH) is used as the oxidant because it is oil-soluble, highly oxidative, thermostable (>80°C) and used for industrial continuous processes [ 22–24 ]. As shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The influence of the solvent on the reaction was further explored, and it was found that the hydrogen-bonding nature of the solvent played a role in the reaction kinetics, with acetonitrile retarding the reaction while dichloromethane did not. 124 ILs are types of solvents that possess unique characteristics that can be modified by altering their organic cation and inorganic or organic anion. Recent research has focused on the application of ILs in ODS reactions, resulting in numerous published papers.…”
Section: Influence Of Reaction Factors On Odsmentioning
confidence: 99%
“…While the product selectivity improved considerably, the reaction kinetics in dichloromethane were found to be faster than those in acetonitrile, despite achieving a lower substrate conversion. The influence of the solvent on the reaction was further explored, and it was found that the hydrogen-bonding nature of the solvent played a role in the reaction kinetics, with acetonitrile retarding the reaction while dichloromethane did not …”
Section: Influence Of Reaction Factors On Odsmentioning
confidence: 99%